Avoiding common errors in the emergency department - Mattu, Amal (Errors series, 2010)
"Avoiding Common Errors in the Emergency Department" succinctly describes 400 errors commonly made by attendings, residents, medical students, nurse practitioners, and physician assistants in the emergency department, and gives practical, easy-to-remember tips for avoiding these pitfalls. This pocket book can easily be read immediately before the start of a rotation or used for quick reference on call. Each error is described in a short clinical scenario, followed by a discussion of how and why the error occurs and tips on how to avoid or ameliorate problems. Areas covered include psychiatry, pediatrics, poisonings, cardiology, obstetrics and gynecology, trauma, general surgery, orthopedics, infectious diseases, gastroenterology, renal, anesthesia and airway management, urology, ENT, and oral and maxillofacial surgery. Sections that focus on non-clinical aspects of emergency medicine practice-such as proper documentation, communication with consultants, and interactions with lawyers-are also included.